Energy Detection Technique In Cognitive Radio Network - Mohamad, Mas Haslinda; Mahmat Sani, Norairin (Engg Journals Publications, 2013)
Energy detection is one of the spectrum sensing techniques in cognitive radio system that facilitate to detect vacancies in spectrum frequency.Energy detection also denoted as non-coherent detection is the signal detection mechanism employing a power detector to determine the availability or nonavailability of signal in the band.In this paper,BPSK modulation signal is generated randomly as the input signal to the energy detector to analyze the spectrum frequency.Probability of detection is obtained throughout the detection process using various numbers of samples and SNR value.